Perancangan Audio Murottal Al-qur’an Untuk Terapi Emosi Anak Autis Menggunakan Metode Human Centered Design - Wahyu Teja Kusuma; Faurika; M. Syauqi Haris; Ahsanun Naseh Khudori (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2023)
One of the characteristics of autistic children or autism spectrum disorder (ASD) is having emotional disturbances. This underlies the design of audio-visual murotal Al-Qur'an as a therapeutic tool for children with autism. Indirectly, murotal Al-Qur'an can calm children's emotions. This study aims to design practical audio-visual-based media for autistic children. The method in this study combines the Human Centered Design (HCD) method, persona, and expert validation. This research cycle begins with pre-production, production to the final result in the form of an audio-visual media design for the emotional therapy of autistic sufferers. The design of the audio-visual media was tested using the expert validation method with functional testing so that the results of the audio-visual media design from this study were by the requirements.